Exploring the Connection Between Facial Skin Cleansing Habits and Acne Vulgaris: A Comprehensive Review - Sari, Anna Rahmania; Ramadhanty, Prajnya Kamila; Anggraeni, Natasha; Destra, Edwin; Firmansyah, Yohanes (Medicor : Journal of Health Informatics and Health Policy, 2023)
Acne Vulgaris (AV) is a chronic inflammatory condition affecting the pilosebaceous follicles, characterized by multifactorial causative factors and clinical manifestations such as cysts, pustules, comedones, nodules, and papules. While AV is not life-threatening, it can significantly impact an individual's well-being by reducing self-esteem, increasing anxiety, and affecting their economic and social life. This paper conducts a comprehensive analysis of existing literature, synthesizing information from multiple reputable sources. The main objective of this review is to explore the implementation of treatments related to the relationship between skin cleansing habits and Acne Vulgaris. The connection between facial skin hygiene and the occurrence of Acne Vulgaris is of significant interest. One key aspect is the potential reduction in Acne Vulgaris when individuals maintain good facial skin hygiene practices. When facial skin is cleaned appropriately, it hinders the accumulation of excess sebum, one of the contributing factors to the development of Acne Vulgaris. It is essential to acknowledge the variability in research outcomes. While certain studies propose that excessive facial cleansing may worsen Acne Vulgaris due to potential skin irritation and glandular complications, others recommend a minimum of twice-daily facial cleansing with a gentle cleanser to maintain skin well-being. The optimal cleansing frequency may depend on individual skin conditions and the presence of comedonal lesions.